Realization of Combined Chromatic Dispersion Compensation Methods in High Speed WDM Optical Transmission Systems - Spolitis, S.; Ivanovs, G. (Elektronika ir Elektrotechnika, 2011)
Chromatic dispersion (CD) has a significant impact on a quality of transmitted optical signal in high-speed fiber optic communication systems with data rates up to 10 Gbit/s, and as a result CD limits the maximum length of transmission distance. In order to operate fiber optic communication system with a sufficiently low bit error ratio (BER) and minimize the performance degradation caused by pulse distortion and broadening, dispersion compensation is needed. In this work using OptSim simulation software we realize an experimental high-speed WDM fiber optic communication system model with a new combined dispersion compensation mechanism where a conventional dispersion-compensating fiber (DCF), fiber Bragg grating (FBG) or optical phase conjugator (OPC) are used together. The best results were obtained by using FBG-OPC dispersion compensation scheme which showed the lowest BER value. Basis of the results we recommend avoiding the use of DCF for CD compensation where it is possible and use FBG instead. Ill. 15, bibl. 9 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.113.7.622